Determinação do coeficiente de dispersão em rios, através de traçadores radioativos e fluorescentes - Rosso, Thereza Christina de Almeida (1986)
The purpose of this work was to determine experimentally the dispersion coefficient in natural streams through the aplication of radioactive and fluorescent tracers. The technique used to obtain the experimental data was the simmultaneous injection of the radioactive tracer Bromim 82 and the fluorescent ones, Amidorodamine G. extra and Uranine. A comparison among these different tracers is shown as well as the performance of Uranine in a poluented stream in the presense of suspended sediments. The site chosen for the experiments was the Piabanha River, between Pedro do Rio and Areal, located at Rio de Janeiro state, in a nearly 20 km strech.